Clinical use of controlled oxygenated rewarming of kidney grafts prior to transplantation by ex vivo machine perfusion. A pilot study. (8th November 2021) - Zlatev, Hristo; von Horn, Charlotte; Kaths, Moritz; Paul, Andreas; Minor, Thomas
Abstract: Background: Sudden restoration of normothermic conditions upon reperfusion of cold‐stored grafts has been suggested to entail a massive energy demand not yet met by the cells that still suffer from hypothermic torpor. An adapted and gentle rise of graft temperature by ex‐vivo machine perfusion has, therefore, been proposed. This should now be tested in the clinical setting. Methods: In a first clinical series, six ECD‐kidneys were subjected to controlled oxygenated rewarming (COR) during short term pre‐implantation machine perfusion. Matched kidneys that were conventionally kept on ice served as controls. Results: Early allograft function after transplantation was significantly improved by COR. On post‐operative day 7, clearance of creatinine was more than twofold higher after COR and fractional excretion of sodium in the normal range, while significantly elevated in control kidneys. Good correlations were seen between ulterior graft function and real‐time parameters obtained during pre‐transplant machine perfusion (Lactate: r 2 = .9; TIMP2: r 2 = .74). Conventional denominators of graft viability like kidney donor risk index KDRI were far less predictive ( r 2 = .26). Conclusion: It is concluded that COR can be safely applied to renal grafts and appears to be a valuable tool to predict and improve early renal function after transplantation.